Pre-Service English Teachers’ Professional Identity Development: A Case Study - Sry Mora Yuni Siahaan; Adaninggar Septi Subekti (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2021)
The present study was conducted to investigate the development of the professional identity of Indonesian pre-service teachers of English as they served as lecturer assistants through a qualitative case study. The participants of the study were five lecturer assistants and five students taught by the lecturer assistants at an English Education major in the first semester of the 2020/2021 academic year. The method employed was conducting online semi-structured interviews. Through Thematic Analysis, the study found that the lecturer assistant participants trained their communication skills with their students by experiencing teaching firsthand. It was also found that the experience of being lecturer assistants facilitated the assistant participants to realise the importance of building rapport with their students and have more insights into the teaching profession. In a similar vein, the student participants also agreed that their lecturer assistant had successfully, albeit gradually, built rapport with them. The assistant participants were also reported to have better classroom management as the semester progressed. Based on the findings, possible implications and contributions were stated with possible limitations and suggested directions for future studies in the field of teacher professional identity development.